Difluprednate 0.05% versus Prednisolone Acetate 1% for Endogenous Anterior Uveitis: Pooled Efficacy Analysis of Two Phase 3 Studies. (3rd April 2019) - Sheppard, John D.; Foster, C. Stephen; Toyos, Melissa M.; Markwardt, Kerry; Da Vanzo, Robert; Flynn, Thomas E.; Kempen, John H.
ABSTRACT: Purpose : To analyse pooled data from 2 similar phase 3 noninferiority studies comparing difluprednate 0.05% versus prednisolone acetate 1% in patients with endogenous anterior uveitis. Methods : Patients received difluprednate alternating with vehicle or prednisolone acetate for 14 days (8 drops/day in both groups), followed by tapering from day 14 to 28. All patients were observed until day 42. Results : More patients on difluprednate than on prednisolone acetate were cleared of anterior chamber cells on day twenty one (71.3% vs 54.7%; p = 0.02); results were similar at the other time points. Treatment withdrawals were higher with prednisolone acetate than difluprednate (19.8% vs 7.4%; log-rank p = 0.02). Study discontinuation due to lack of efficacy was also higher with prednisolone acetate than difluprednate (14.0% vs 0%; p = 0.0002 [pre-specified exploratory analysis]). Conclusions : More difluprednate-treated eyes were quiet following 21 days of treatment, and difluprednate-treated patients were much less likely to be withdrawn from the study because of treatment failure.